Spanish youth is emigrating: A bibliometric approach to the media coverage. - Clara Selva; Aniol Recordà (PLoS ONE)
Recent years have witnessed the emigration of young Spanish people searching for labor opportunities. A decade after the beginning of the worldwide economic crisis in 2007, the rapid deterioration of living conditions and lack of opportunities for personal development combined with the breakdown of professional expectations have led thousands of young people to emigrate from Spain, creating the so-called youth exodus. The press has paid recurrent attention to this phenomenon, often using eye-catching headlines such as 'Brain Drain'. Given the regular interest of the media in this phenomenon, the objective of this research is to analyze the media coverage of the drain of Spanish talent capital, or the emigration of young Spanish people seeking a better future, to create a distributive map that defines the characteristics and trends of this coverage. The analyzed corpus comprises 346 articles from eight Spanish and eleven international newspapers. The articles were coded based on descriptive variables (i.e., author, publication year, newspaper and language) and categorical variables (i.e., section, method, approach to the phenomenon, assessment of the phenomenon and overview of the phenomenon). The results indicate a significant increase in press coverage over the past few years and reveal associations between assessment of the phenomenon and year and between assessment of the phenomenon and section. As a result of this research, new investigative lines are unveiled regarding the social construction of the phenomenon in the media and the identity and individual construction of the 'truncated careers' of young Spanish people.